Asparaginase-Associated Pancreatitis in Acute Lymphoblastic Leukemia: Results From the NOPHO ALL2008 Treatment of Patients 1-45 Years of Age - Rank, Cecilie U. (J Clin Oncol, 2020)
PURPOSE: Asparaginase-associated pancreatitis (AAP) is common in patients with acute lymphoblastic leukemia (ALL), but risk differences across age groups both in relation to first-time AAP and after asparaginase re-exposure have not been explored. PATIENTS AND METHODS: We prospectively registered AAP (n = 168) during treatment of 2,448 consecutive ALL patients aged 1.0-45.9 years diagnosed from July 2008 to October 2018 and treated according to the Nordic Society of Pediatric Hematology and Oncology (NOPHO) ALL2008 protocol. RESULTS: Compared with patients aged 1.0-9.9 years, adjusted AAP hazard ratios (HRa) were associated with higher age with almost identical HRa (1.6; 95% CI, 1.1 to 2.3; P = .02) for adolescents (10.0-17.9 years) and adults (18.0-45.9 years). The day 280 cumulative incidences of AAP were 7.0% for children (1.0-9.9 years: 95% CI, 5.4 to 8.6), 10.1% for adolescents (10.0 to 17.9 years: 95% CI, 7.0 to 13.3), and 11.0% for adults (18.0-45.9 years: 95% CI, 7.1 to 14.9; P = .03). Adolescents had increased odds of both acute (odds ratio [OR], 5.2; 95% CI, 2.1 to 13.2; P = .0005) and persisting complications (OR, 6.7; 95% CI, 2.4 to 18.4; P = .0002) compared with children (1.0-9.9 years), whereas adults had increased odds of only persisting complications (OR, 4.1; 95% CI, 1.4 to 11.8; P = .01). Fifteen of 34 asparaginase-rechallenged patients developed a second AAP. Asparaginase was truncated in 17/21 patients with AAP who subsequently developed leukemic relapse, but neither AAP nor the asparaginase truncation was associated with increased risk of relapse. CONCLUSION: Older children and adults had similar AAP risk, whereas morbidity was most pronounced among adolescents. Asparaginase re-exposure should be considered only for patients with an anticipated high risk of leukemic relapse, because multiple studies strongly indicate that reduction of asparaginase treatment intensity increases the risk of relapse.